2019
DOI: 10.3390/electronics8060657
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Degradation Rate on the Irradiated Double-Polysilicon Self-Aligned Bipolar Transistor

Abstract: The latent enhanced low dose rate sensitivity (ELDRS) effect is observed in the double-polysilicon self-aligned (DPSA) technology PNP bipolar junction transistor (BJT) irradiated with a high and low dose rate gamma ray, which is discussed from the perspective of the three-stage degradation rate of the excess base current. The great degradation rate as a result of the high dose irradiation of the first stage is dominantly ascribed to the positive oxide trap charges accumulated during a short irradiation, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Results of the investigation confirmed the achievement of excellent radiation hardness and decent specific on-resistance for the device. Article [2] discussed the mechanism of degradation on the Irradiated Double-Polysilicon Self-Aligned Bipolar Transistor with a dose rate of 50 rad (Si)/s and 0.05 rad (Si)/s. The comparison of the high and low dose rate showed that the increase of the base current caused by low dose rate irradiation was larger than that caused by high dose rate irradiation, resulting in greater current gain degradation than that caused by the high dose rate, highlighting that the ELDRS effect may occur.…”
Section: The Present Issuementioning
confidence: 99%
“…Results of the investigation confirmed the achievement of excellent radiation hardness and decent specific on-resistance for the device. Article [2] discussed the mechanism of degradation on the Irradiated Double-Polysilicon Self-Aligned Bipolar Transistor with a dose rate of 50 rad (Si)/s and 0.05 rad (Si)/s. The comparison of the high and low dose rate showed that the increase of the base current caused by low dose rate irradiation was larger than that caused by high dose rate irradiation, resulting in greater current gain degradation than that caused by the high dose rate, highlighting that the ELDRS effect may occur.…”
Section: The Present Issuementioning
confidence: 99%
“…In this article, we have used a new model called year-on-year (YOY) developed by the national renewable energy laboratory (NREL). The open access software (RdTools) allows us to analyze the degradation rate for PV installations [2]. The degradation calculations consist of several steps discussed in the following processes:…”
Section: Year-on-year (Yoy) Degradation Analysis Techniquementioning
confidence: 99%
“…Economically, PV modules degradation rates are equally important, because a higher degradation rate interprets directly into less output power produced by the system, thus reducing future cash flows [2]. Inaccuracies in determined degradation rates lead to amplified financial risks in the PV sector.…”
Section: Introductionmentioning
confidence: 99%